Aesthetics of Hybrid Digital Image Technologies in TV Drama: محمد ثائر عدنان البياتي (Al-Academy, 2020)
TV medium derives its formal shape from the technological development taking place in all scientific fields, which are creatively fused in the image of the television, which consists mainly of various visual levels and formations. But by the new decade of the second millennium, the television medium and mainly (drama) became looking for that paradigm shift in the aesthetic formal innovative fields and the advanced expressive performative fields that enable it to develop in treating what was impossible to visualize previously. In the meantime, presenting what is new and innovative in the field of unprecedented and even the familiar objective and intellectual treatments. Thus the TV medium has sought for working aesthetically and functionally with technically superior scientific and engineering fields in order to get to growing and developed levels in the race of the artistic quality towards an innovative and unique dramatic achievement in its pictoral form. This research studies how to achieve the aesthetic work of the new scientific technologies and methods of their hyberdization in the TV image